Evaluating Three Alternative Designs for Reducing Delay at an Intersection in Dohuk, Iraq - Batto, Rafal Faez Hadi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Traffic delay is one of the most important factors used in intersection analysis. This study focused on the average delay by looking at different alternative junction models. These different models analyzed with and without signalization according to cycle length in order to help create alternate designs. Green intervals were optimized to reduce average delay in order to assist the level of service for the given junction. The traffic and geometric data were taken from the Imam Hamza Intersection as a case study. A delay problem in this intersection of Dohuk city (northern Iraq) was analyzed and redesigned under the present conditions of right-of-way and volumes of traffic. Firstly redesign for signalized intersection was done by expanding the roads of each approach. Then designs of three new interchange models were proposed. A forecasting of traffic volumes for the next fifteen years was taken using each design model. The simulations for these new models were taken by applying different scenarios for each model in order to find the best results of delay and level of service. Likewise a comparison was made based on the best amount of delay obtained from these new models. Finally, the level of delay for the peak hours of each model was compared with the current level of delay in the intersection in order to find the total delay hours for next fifteen years and determine the most effective design in terms of reducing delay in the given intersection. The conclusion of this study displayed the second model diamond interchange had the minimum results of delay comparing with the other models. Keywords: Delay, Signalized intersection, Diamond interchange, Imam Hamza Intersection, Level of service, Traffic jam, Delay time cost. ………………………………………………………………………………………………………………………… ÖZ: Kavşak analizinde en önemli etkenlerden biri de trafikte yaşanan gecikmelerdir. Bu araştırma alternatif kavşak modellerini ele alarak ortalama bekleme sürelerinin sonuçlarını mercek altına almayı hedeflemektedir. Bu farklı modeller alternatif tasarımlar yaratmak için sinyal süresine göre hem sinyalizasyon ile hem de sinyalizasyonsuz halde analiz edilecektir. Söz konusu olan kavşağın hizmet seviyesini artırmak için yeşil ışığın süreleri en iyi şekilde kullanılarak ortalama bekleme gecikme süresinin azaltılması amaçlanmaktadır. Trafik ve geometrik veriler örnek olay incelemesi olarak Imam Hamza kavşağından alınacaktır. Irak’ın kuzeyindeki Dohuk şehrinde bulunan bu kavşaktaki bir gecikme problemi mevcut trafiğin sağ şeridi ve trafik yoğunluğunun durumu göz önünde bulundurularak analiz edilip yeniden tasarlanacaktır. Elmas şeklinde köprülü kavşağın üç yeni modelini tasarlamak için önümüzdeki 15 yılın trafik yoğunluk tahminleri dikkate alınacaktır. Aynı şekilde söz konusu olan yeni modeller ile benzer yollardaki gecikme süresi baz alınarak bir karşılaştırma da yapılacaktır. Bu süre miktarı tespit edilince gecikmeden dolayı oluşan maliyet belirlenebilecektir. Son olarak, gelecek 15 yılın toplam gecikme süresini bulmak, en etkili modeli belirlemek ve verilen kavşaktaki gecikme süresini düşürmek için her modelin yoğun saatlerdeki gecikme süresi ve kavşaktaki şimdiki gecikme süresi karşılaştırıldı. Anahtar Sözcükler: Gecikme, siyalizasyonlu kavşak, Elmas şeklinde kavşak, Imam Hamza kavşağı, Hizmet seviyesi, Trafik sıkışıklığı, Gecikme süresi maliyeti.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Mehmet Metin Kunt.
Keywords: Civil Engineering; Traffic Engineering; Delay, Signalized Intersection, Diamond Interchange, Imam Hamza Intersection, Level of Service, Traffic Jam, Delay time cost